Evaluation of Medication Use Pattern Among Patients Presenting to the Emergency Department of Hiwot Fana Specialized University Hospital, Using WHO Prescribing Indicators - Mishore, Kirubel Minsamo; Girma, Yabsira; Tola, Assefa; Mekuria, Abraham Nigussie; Ayele, Yohanes (Frontiers in Pharmacology, 2020)
Background Ensuring rational drug use requires ongoing evaluation of drug prescribing, dispensing, and use by patients. Health care providers working in an emergency department face unique challenges, including making urgent decisions, patient overload, and limited resources, which contribute to inappropriate drug use. Rational medication use should be an important aspect of emergency care to improve patient outcomes. Thus, this study was conducted to assess medication utilization patterns using World Health Organization (WHO) prescribing indicators in the emergency department. Methods A cross-sectional study design was implemented among patients presenting at the emergency department of Hiwot Fana Specialized University Hospital (HFSUH) from January to March 2018. The data were collected from the medical charts of a total of 342 patients using a pre-prepared structured format according to WHO recommendations. The data were analyzed using SPSS version 21 software and presented in tables and figures. Results The most commonly reported clinical diagnosis was found to be soft tissue laceration or abrasion, in 75 patients (21.9%), followed by dyspepsia, in 50 (14.6%), and severe pneumonia, in 44 (12.9%). A total of 810 drugs were prescribed for the 342 patients. The main category of drugs prescribed were analgesics, constituting 125 (29.2%), followed by antibiotics, 120 (28.0%). Regarding WHO prescribing indicators, the average number of drugs prescribed per encounter was 2.36, the number of encounters at which antibiotics were prescribed was 127 (37.13%), and injections were prescribed at 300 (87.7%) encounters. All of the drugs prescribed were from the National Essential Medicine List (NEML) of Ethiopia, and 780 (98.1%) of the drugs were prescribed by international nonproprietary name. Conclusion Overall, there were inflated use of antibiotics and injection drugs, whereas prescribing by international nonproprietary name and prescribing from NEML were according to the recommendations. Hence, the hospital should work to ensure the judicious use of antibiotics and injection drugs.